Prevalence of pain and its association with symptoms of post‐traumatic stress disorder, depression, anxiety and distress in 846 cancer patients: A cross sectional study. Issue 4 (3rd December 2020) - Unseld, Matthias; Zeilinger, Elisabeth L.; Fellinger, Matthäus; Lubowitzki, Simone; Krammer, Katharina; Nader, Ingo W.; Hafner, Matthias; Kitta, Anna; Adamidis, Feroniki; Masel, Eva K.; Preusser, Matthias; Jäger, Ulrich; et al.
Abstract: Objective: Pain depicts a severe physical symptom but its relationship to mental health problems is not well studied in cancer patients. The aim of this study was to investigate the prevalence of pain and its correlation with symptoms of post‐traumatic stress disorder (PTSD), depression, anxiety and psychological distress in a large sample of cancer patients. Methods: From 2010 to 2019, cancer patients who received outpatient treatment at the Medical University of Vienna were assessed with the Post‐Traumatic Symptom Scale (PTSS‐10) and the Hospital Anxiety and Depression Scales. A visual analogue scale was used to assess pain perception. For statistical analysis, linear regression models were applied to log‐transformed data. Results: Of the 846 cancer patients included in the study, 63.5% experienced pain (mild 43.5%, moderate 13.6%, severe 6.4%). About a third (31.2%) of the total sample presented with significant PTSD symptoms. Significant symptoms of depression, anxiety and distress were present in 13.9%, 15.1% and 25.3%, respectively. Women more often reported symptoms of PTSD, anxiety and distress. Pain scores were significantly related to symptoms of PTSD, depression and psychological distress (all with p < .001), but not to anxiety. Conclusions: Results show a high prevalence of experienced pain and indicate a clear association of elevated pain levels with psychiatric symptoms in oncological patients in a large Austrian sample. In order to decrease experienced pain and to enable better treatment of mental health problems in cancer patients, diagnostic procedures and interventions based on a biopsychosocial model need to be intensified.